Enhancing Students’ Motivation and Critical Thinking through Problem-Based Science Magazines in Ecology and Biodiversity Learning - Mulyati, Yayuk; Ula, Nurin Ni’matul; Hasan, Said; Putri, Novi Eka; Ardiansyah, Angga; Winarmi, Nasrunniati Dyahayu Anggi (Indonesian Journal of Biology Education, 2025)
Critical thinking and learning motivation are essential competencies for 21st-century students; however, these skills remain relatively low in science education due to teacher-centered instruction and the limited use of engaging media. To address this issue, innovative approaches that integrate effective learning models with appealing learning resources are required. This study investigates the effect of incorporating a Problem-Based Learning (PBL) science magazine on junior high school students’ learning motivation and critical thinking skills in ecology and biodiversity. A quantitative research design was applied using a pretest–posttest control group design, involving two groups of students including an experimental class that used a PBL-based science magazine and a control class that employed a discovery learning worksheet. The results of the independent sample t-test revealed statistically significant differences between the two groups. Furthermore, the N-Gain test demonstrated high effectiveness, with an N-Gain score of 0.71 for learning motivation and 0.70 for critical thinking skills. These findings suggest that the integration of PBL-based science magazines has a substantial positive impact on students’ learning motivation and critical thinking, highlighting the potential of combining innovative models and media to strengthen science learning outcomes.